RUSSIAN HIGHER EDUCATION SYSTEM IN THE BOLOGNA PROCESS(On the materials of the Russian Federation National Report for the EHEA Ministerial Conference) - Yulia D. Artamonova; Artur L. Demchuk; Nadezhda R. Kamynina; Igor B. Kotlobovsky (Moscow Polytechnic University, 2016)
The article describes the major issues of the European Higher Education Area development in the context of the Yerevan Ministerial Conference and the Fourth Bologna Policy Forum (May 2015), and the place of Russia in the European Higher Education Area.